Materials science and engineering properties - Gilmore, Charles M. (Cengage Learning, 2015)
This text is primarily aimed at mechanical and aerospace engineering students, building on actual science fundamentals before building them into engineering applications. Even though the book focuses on mechanical properties of materials, it also includes a chapter on materials selection, making it extremely useful to civil engineers as well.